Measurement of CP asymmetry in B0s→D-/+sK+/- decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Grünberg, Oliver; et al. (Journal of high energy physics, 2014)
We report on measurements of the time-dependent CP violating observables in Bs0 → Ds∓K± decays using a dataset corresponding to 1.0 fb−1 of pp collisions recorded with the LHCb detector. We find the CP violating observables Cf = 0.53±0.25±0.04, A∆Γ f = 0.37±0.42±0.20, A∆Γ f¯ = 0.20±0.41±0.20, Sf = −1.09±0.33±0.08, Sf¯ = −0.36 ± 0.34 ± 0.08, where the uncertainties are statistical and systematic, respectively. Using these observables together with a recent measurement of the Bs0mixing phase −2βsleads to the first extraction of the CKM angle γ from Bs0 → Ds∓K± decays, finding γ = (115− 43+ 28)° modulo 180° at 68% CL, where the error contains both statistical and systematic uncertainties.